A review of the whitefly genus Aleurocanthus Quaintance & Baker (Hemiptera: Aleyrodidae) in Australia - Gillespie, Peter S. (Zootaxa, 2012)
A review of the genus Aleurocanthus in Australia recognises 22 species, of which eleven new species are described here- A. ashleyi sp. n., A. callistemonus sp. n., A. coombsi sp. n., A. gullanae sp. n., A. laurenae sp. n., A. maculatus sp. n., A.mcneili sp. n., A. neofroggatti sp. n., A. octospinosum sp. n., A. sapindus sp. n. and A. schmidti sp. n. recorded from theAustralian mainland for the first time is A. luteus Martin, whilst the presence of A. woglumi Ashby is confirmed from anAustralian territory (Christmas Island, Indian Ocean) and from Daru Island in the Torres Strait. Distributional, biological and host data are presented for Aleurocanthus species in Australia, and a key to species is given.